1983
DOI: 10.1002/1097-0142(19830615)51:12<2220::aid-cncr2820511212>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Serumβ2-microglobulin in malignant lymphoma

Abstract: Serum β2‐microglobulin (S‐β2m) was measured at diagnosis in 189 patients with malignant lymphoma, all with a normal serum creatinine clearance. The diagnosis was non‐Hodgkin's lymphoma (NHL) in 149 patients and Hodgkin's disease (HD) in 40. Among the NHL group, S‐β2m was raised (>3.0 mg/1) in 15% of patients with Stage I and II and in 65% of those with Stage III and IV. The corresponding frequencies for HD were 11% and 83% respectively. In NHL, a high pretreatment level of S‐β2m was found to be a poor prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 18 publications
4
25
0
1
Order By: Relevance
“…The considerably lower risk of recurrence and longer duration of remission in patients with normal P-2 microglobulin levels also accord with the results of previous smaller studies (Hagberg et al, 1983). Once again it may be postulated that this relates to the effectiveness of host immune surveillance.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The considerably lower risk of recurrence and longer duration of remission in patients with normal P-2 microglobulin levels also accord with the results of previous smaller studies (Hagberg et al, 1983). Once again it may be postulated that this relates to the effectiveness of host immune surveillance.…”
Section: Resultssupporting
confidence: 87%
“…Previous studies in non-Hodgkin's lymphoma have shown a correlation between stage of disease and P-2 microglobulin level (Spati et al, 1978;Child et al, 1980;Hagberg et al, 1983;Legros et al, 1987) (Moller et al, 1986), and that changes in HLA complex proteins which impair light and heavy chain association result in enhanced release of P-2 microglobulin (Ferrier et al, 1985;Rein et al, 1987).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This may be due to more active cellular proliferation in tumours with poorer histological differentiation. Similar findings however were not evident in non-Hodgkin's lymphoma (Anderson et al, 1983 (Teasdal et al, 1977) and myeloma (Hagberg et al, 1983;Alexanian et al, 1985), and is thought to be due to increased cell turnover (Karlsson et al, 1980) and/or augmented immune response by lymphocytes to the neoplasm (Forman, 1982;Rashid et al, 1980;Karlsson et al, 1980;Shuster et al, 1976).…”
mentioning
confidence: 86%
“…Cell membrane turnover is the principle source of P2M in blood, plasma and body fluids (Cresswell et al, 1974;Forman, 1982). Elevated serum levels has been found to be associated with increasing age, renal impairment (Bailey et al, 1978) and a variety of malignancies and appears to be a reflection of tumour load in patients with lymphoma (Anderson et al, 1983;Hagberg et al, 1983), myeloma (Child et al, 1983;Norfolk et al, 1980;Alexanian et al, 1985), lung cancer (Schweiger & Tocsanyi, 1978), breast cancer (Teasdal et al, 1977;Rashid et al, 1980), and squamous cell carcinoma of the head and neck (Wennerberg et al, 1984 (Ho et al, 1976). Although P2M has a high sensitivity in metastatic disease, the clinical relevance in this situation is limited.…”
mentioning
confidence: 99%